CULTIVATING CHARACTER EDUCATION BASED ON SUNDANESE CULTURE LOCAL WISDOM - Aan Hasanah; Neng Gustini; Dede Rohaniawati (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2016)
This study was aimed at determining the role of city government in cultivating character values based on Sundanese culture local wisdom to develop students’ life skill; describing the process, and impact of character values education; investigating both supporting and inhibiting factors of character values education process in developing students' life skills. This study which applied case study was conducted at public and private madrasah aliyah in Bandung. The finding shows that the city government plays important role in developing the Sundanese culture-based character values by issuing a policy in the form of Regulation No. 9 of 2012 concerning the use and preservation of language, literature, and Sundanese script. Madrasah aliyah used learning and mentoring to implement character education program. Character education is supported by several factors and this study found some factors inhibiting character education process.